Understory light availability in stands of Abies religiosa - Plateros-Gastélum, Pedro Antonio; Reyes-Hernández, Valentín José; Velázquez-Martínez, Alejandro; Hernández de la Rosa, Patricia; Campos-Ángeles, Gisela Virginia (Instituto de Ecología, A.C., 2018)
The availability of light is one of the main factors that influences the establishment and development of plant species in the forest understory. In order to characterize the light environment and canopy structure, and their relationships with understory plant diversity, sampling sites were established in pure Abies religiosa (Kunth) Schltdl. et Cham. stands in Aquixtla, Puebla. In these sites, information useful to evaluate stands characteristics, namely basal area, tree density, and quadratic mean diameter was collected. Also, canopy structural characteristics, in particular, leaf area index, canopy opening fraction, and light transmission index, were estimated from hemispherical photographs taken onsite and analysed with the software GLI®. Understory light environment indicators were also estimated, namely direct and diffuse radiation, sunflecks distribution and frequency, sunpatches, sungaps, and clearings, as well as cumulative average daily sunflecks and average sunflecks duration. Relationships among the variables estimated were determined with Pearson’s correlation coefficient and with simple linear regression. Results showed a significant and strong relationship between canopy structure and solar radiation parameters (p < 0.001), while stand structure and light parameters (p < 0.05) showed a low correlation (r ≈ 0.50). Canopy opening fraction was the most powerful explanatory variable for leaf area index, direct and diffuse radiation available in the understorey, as well as for canopy light transmission rate. The variability of the understory light regime for these stands was better explained by canopy structure parameters than by stand structural characteristics.